Safety evaluation method of composite girder cable-stayed bridge based on structural health monitoring system. (19th November 2019) - Zhang, Kun; Zong, Zhouhong; Liao, Yuchen; Fan, Xingchen; Niu, Jie
A comprehensive safety evaluation method which can dynamically reflect the damage changes in operation state is established based on the structural health monitoring (SHM) system of a composite girder cable-stayed bridge. The fuzziness and uncertainties during the evaluation process are considered and the random errors are reduced by using the proposed evaluation method. The normal values and safety limits of monitoring indexes of the Guanhe Bridge are proposed by using numerical simulation and monitoring data statistics of the baseline finite element model, and the index evaluation standard of the related code requirements. The results can be used to complement the lack of online monitoring indexes in the existing regulations, and solve the problem that lacking support for quantitative monitoring data in current bridge management system evaluation module, which can provide theoretical basis for the evaluation, management, maintenance and decision-making of bridge structures.